ANALISIS RISIKO KEJADIAN BERAT BAYI LAHIR RENDAH (BBLR) PADA PRIMIGRAVIDA - Hidayatush Sholiha; Sri Sumarmi (Universitas Airlangga, 2015)
Low birth weight (LBW) babies still become a problem in developing countries. LBW increase risk of mortality and morbidity. The prevalence of LBW in Probolinggo increased from 2011 to 2013. This study aims to analyze risk factors related to LBW in primigravidae. This study used case control design and purposive sampling technique. The variables include age of pregnant mothers, mother’s education level, family income, gestational age, frequency and quality of antenatal care, and food taboo. Data was analyzed using chi-square and multivariate regression logistic (α=0.05). Factors associated to LBW were the gestational age (p=0.000), age at pregnancy (p=0.030), and level of education (p=0.023). Regression logistic analysis showed that gestational age is a risk factor of LBW (OR= 66; CI 95% 8.197 to 531,391). Mother who gave birth at the age of preterm (<37 weeks gestation) have 66 times greater risk of having LBW baby in primigravidae compared to mothers who gave birth at the age of aterm. Mothers and brides’ woman are expected to avoid pregnancy at risk age (<20 years and >35 years) and the socialization of risk factors related to high risk of pregnancy is needed to reduce the risk of LBW.Keywords: gestational age, low birth weight, primigravidae